Cultural Tourism Prospects of Bhaleswor Mahadev of Chandragiri Area, Kathmandu - Sigdel, Achyut (Nepalese Culture, 2024)
This paper makes an attempt to examine prospects of cultural tourism of Bhaleswor Mahadev in Chandragiri area of Kathmandu by applying cultural heritage studies perspectives. It is a cultural study of completely qualitative nature. Throughout the world, the tourism industry has been an economic generator including conserving the heritage sites. The study area is Chandragiri municipality - 4 and the major historical and religious sites in the foothill of Mahabharat hill range of Chandragiri. Bhaleswor Mahadev temple is situated on the top of the Chandragiri hill in the southwest of Kathmandu valley in 13 km. The shape of the hill looks like a Bhale (rooster) and Nilkantha Mahadev stayed in this hill for some time and at that time heard the sound of rooster so this Mahadev is called Bhaleswor Mahadev. Due to this temple, pilgrims and tourists are increasing day by day to go to Chandragiri hill through cable car. Bhaleswor Mahadev temple and Chandragiri cable car add more benefit in promotion of cultural tourism of Chandragiri area. One can easily go to worship Bhaleswor Mahadev through cable car within twelve minutes. One can observe spectacular view of the Himalayan range of Annapurna range, Langtang range, Everest and other mountains like Cho Oyu, Gaurisankhar etc from the top of the hill. Chandragiri cable car is the second commercial cable car of Nepal. Chandragiri area is very important from historical, cultural and archaeological point of view. The other major historical and religious sites of Chandragiri area in the foothill of Mahabharat hill range are Mahalaxmi Temple, Chandanvarateswor Mahadev, Matatirtha and Machchhe Narayan. These sites give more importance in the development of cultural tourism of Chandragiri area. Despite these studies, there is still hardly found scholarship of cultural tourism prospects of Bhaleswor Mahadev in Chandragiri area, Kathmandu. Therefore, this paper aims to address the gap of cultural tourism of Chandragiri area.